Transitioning from pediatric to adult care and the HIV care continuum in Ghana: a retrospective study - Pearl Abaka; Jerry John Nutor (BMC, 2021)
Abstract Background In Sub-Saharan Africa, there are now a significant number of adolescents living with HIV (ALHIV), due to increased access to effective antiretroviral therapy. However, these adolescents are at high risk of dying during the transition to adult care due to various reasons, including lack of preparation for the transition and poor transition arrangements. More knowledge about this issue will lead to a better planned healthcare transition process and preparation for transition from pediatric care to adult care. The aim of this study was to explore the healthcare transitional experiences of ALHIV as they moved from pediatric to adult care. Methods A descriptive exploratory qualitative study was conducted. Purposive sampling method was used to recruit adolescents between 12 and 19 years old. Saturation was realized by the 10th participant. Data were analyzed using thematic content analysis. Results Four main themes emerged from the interview data: the transition process, factors facilitating the transition experience, challenges and coping mechanisms of the ALHIV during transition, and suggestions for improvement based on perceptions on the current transitioning approach. A key finding of this study was the sudden preparation for transition, linked to the absence of a structured transition protocol. Even though age was the main reason for transferring the participants from the pediatric to adult clinic, participants' age did not influence whether they attended clinic appointment on their own or accompanied by a care provider; it was dependent on the availability of their parents or caregivers. Participants' parents and adult family caregivers were also integrated into the transition process to some extent. We also found that most of the participants had good patient-provider relationship with their health care providers in both pediatric and adult clinics. Conclusion Findings support the need to develop a structured healthcare transition policy and age-appropriate transition within the clinic environment. There is also a need for social and community support as ALHIV transition from pediatric to adult care.